Clima organizacional en el personal de salud del Hospital de contingencia II-2 Tarapoto, San Martín, Abril - Setiembre, 2016 - Requejo Villegas, Christian Denys (2016)
Objective: To know the organizational climate in the health personnel of the Contingency Hospital II-2 Tarapoto, San Martín. Materials and Methods: Quantitative, transverse study of descriptive, observational type. Assistance and administrative staff were included. We surveyed 226 workers who met the selection criteria, through simple random sampling. The instrument was a questionnaire of 55 questions that measure 11 dimensions immersed in three variables, human potential, organizational design and organizational culture. An unhealthy climate was estimated at 55 to 128, weather to improve from 129 to 202 and healthy climate from 203 to 275. Results: The organizational climate perceived by the health staff of the Contingency Hospital improved with a score of 173.35. 20.8% perceived a healthy climate, 70.4% to improve and 8.8% unhealthy. Only the identity dimension was perceived as healthy climate, the others a climate to improve, the three variables, human potential, organizational design and organizational culture were climate for improvement. Conclusion: This research shows that workers perceive a climate to improve, which indicates that strategies should be developed to strengthen the organization and improve productivity